ROLE OF PROFESSIONAL SELF-EXPRESSION OF HIGH SCHOOL TEACHERS IN DEVELOPMENT OF MODERN UNIVERSITY - Tarasova, Irina Vladimirovna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The article is devoted to studying the problem of professional self-expression of university teacher. Thesis about the existence of 6 cognitive attributes of the university teacher’s self expression was theoretically identified and empirically acknowledged as a concept: 1) representation of a particular level of people’s self-conscience including professional; 2) describing method, by which a person shows, regulates his activity during objectivation in professional work; 3) acting as the cognitive model of conducting cognitive activity of ethnos, society, individual in natural language ; 4) multiple meaning expression of particular level of individual’s experience and knowledge; 5) emotionality, personal identifying, having subjective and personal judicious and emotional personal meaning, verbal and non-verbal method of expression through reputation, behavior, reactions and etc.; 6) dependence from both teacher’s general culture and particular aspects. The system of criterion of university teacher’s self expression and their indicators was proposed. This approach allowed showing the role of university teacher self-expression in the development of a university through identifying the influence of every university teacher professional self-expression level (external – image building, social professional, creative reformative) on the university development.